Inhibition of Candida albicans growth by steeping freeze-dried robusta ground coffee - Purwanto, Purwanto; Sagita, Yoan Ayung; Lestari, Pujiana Endah; Praharani, Depi; Jani, Yahya; Yaro, Abubakar (Coffee Science - ISSN 1984-3909, 2020)
Coffee contains active compounds that alleged to have antifungal activity. This study aimed to analyze inhibitory effect of steeping freeze–dried Robusta ground coffee (SFDRGC) to the growth of oral microorganism Candida albicans (the main causative agent of oro-pharyngeal opportunistic infection). This is an in vitro experimental study using the post–test only control group design. Serial dilutions of SFDRGC were studied. An antifungal drug Nystatin was used as a positive control, and sterile distilled water as a negative control. The inhibitory effect was study by means of Agar well diffusion method. Result showed that SFDRGC demonstrated antifungal activity. The higher concentration of SFDRGC showed the higher antifungal activities significantly (P < 0.05). Concentration of 100% SFDRGC showed anti-candida activity as potent as Nystatin. In conclusion, 100% SFDRGC demonstrated a potent antifungal agent against C. albicans. This study suggested that coffee beverage might be used as anti-candida mouthwash to prevent the risk of oral opportunistic infection. Further studies, however are needed to confirm this notion, such as epidemiological, and phytochemical studies of antifungal bioactive components in coffee that are processed using various methods. Key words: Agar well diffusion method; antifungal; nystatin; opportunistic infection.